2012
DOI: 10.4314/sajas.v42i4.2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of RRR-α-tocopherol succinate on the meat quality and antioxidative status in broilers

Abstract: ________________________________________________________________________________ AbstractThe objective of this study was to compare the effects of two esters of α-tocopherol, all-rac-α-tocopherol acetate (DL-α-TOA) and RRR-α-tocopherol succinate (D-α-TOS), on meat quality and the antioxidative status in chicks. A total of 320 day-old Arbor Acres broiler chicks were randomly allocated to 4 treatments, each consisting of 8 pens of 10 chicks per pen. Birds in the control group received the basal diet supplemented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 58 publications
1
5
0
Order By: Relevance
“…Average lightness values (L*) obtained in this study (Table 4) ranged between 48 and 50, and therefore, can be considered normal, according to Qiao et al (2001) findings (normal = 48 < L* > 53).The treatments did not influence L*, a* and b* values, which are consistent with the results of Zhang et al (2012), when evaluating the supplementation of broilers diets with different levels of α-tocopherol acetate.…”
Section: Effects Of the Dietary Supplementation Of Sucupira (Pterodonsupporting
confidence: 83%
“…Average lightness values (L*) obtained in this study (Table 4) ranged between 48 and 50, and therefore, can be considered normal, according to Qiao et al (2001) findings (normal = 48 < L* > 53).The treatments did not influence L*, a* and b* values, which are consistent with the results of Zhang et al (2012), when evaluating the supplementation of broilers diets with different levels of α-tocopherol acetate.…”
Section: Effects Of the Dietary Supplementation Of Sucupira (Pterodonsupporting
confidence: 83%
“…In agreement with our results, O’Grady et al (2001) reported that dietary supplementation with 300 IU/kg of DL-α-tocopheryl acetate for 55 day pre-slaughter resulted in improvement in GSH-Px activity in beef. Additionally, Zhang et al (2012a) concluded that the improvement of GSH-Px activity in chicken was due to 30 mg/kg and 60 mg/kg of dietary RRR-α-tocopherol succinate diet supplementation. On the contrary, Lauridsen et al (1999) found that dietary supplementation with DL-α-tocopheryl acetate did not significantly influence GSH-Px activity in muscles of pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Water holding capacity of meat is directly related to the intramuscular lipids and moisture content of the meat (Huff‐Lonergan & Lonergan, ). The inability of meat to bind water leads to decrease in muscle tenderness and increase in cooking loss (Zhang, Wang, Zhou, & Wang, ). Conversely, in the study by Zhang et al (), it was reported that dietary supplementation of vitamin E at 30 and 60 mg/kg can reduce the rate of surface discoloration in chicken meat.…”
Section: Birdsmentioning
confidence: 99%
“…Water holding capacity of meat is directly related to the intramuscular lipids and moisture content of the meat (Huff-Lonergan & Lonergan, 2005). The inability of meat to bind water leads to decrease in muscle tenderness and increase in cooking loss (Zhang, Wang, Zhou, & Wang, 2012).…”
Section: Meatmentioning
confidence: 99%